Microsoft Office Access 2003, Illustrated Brief - Lisa Friedrichsen (Cengage Learning, Inc, 2006)
Part of the Illustrated series, this text offers a visual, flexible way to build Microsoft Access 2003 skills. With unambiguous coverage of basic topics--just 4 units--in a succinct manner, students learn essential Access concepts by following the clear instruction in preparation for more advanced classroom or independent learning